Riflessioni pedagogiche a partire dalle mense scolastiche: l’importanza di ascoltare le voci dei bambini - Dalledonne Vandini, Chiara; Antonelli, Fulvia (Studi sulla Formazione/Open Journal of Education, 2025)
The school canteen is a place where educational, social, cultural, and publichealth dimensions intersect. The PNRR ONFOODS project, in collaboration with the SUSFOODEDU group at the University of Bologna, explores food practices and representations within the school context. This contribution focuses on the “voice” of children and their personal experiences regarding the school canteen. The reflections derive from ethnographic observation and participatory research carried out in four schools in the Bologna area. Listening to children’s voices offers access to a new understanding of school mealtimes and can guide the development of reflective paths to make this daily school experience more meaningful.